Pipeline embolization device implantation in large carotid cavernous aneurysm associated with situs inversus totalis - Chakravarthi, Sudheer (Interv Neuroradiol, 2019)
Situs anomalies are a heterogenous class of inborn visceral and vascular abnormalities with a broad range of radiographic characteristics. Situs inversus totalis is characterized by mirror image location of the heart and viscera relative to situs solitus (normal position). Few aberrations involving the neuraxis, and rarely intracranial aneurysms, have been reported in association with situs inversus totalis. We describe the radiological findings and endovascular management of one of the first of its kind: the association of bilateral carotid cavernous aneurysms (one large and the other small-sized) with situs inversus totalis.